2007
DOI: 10.1080/00220380701259665
|View full text |Cite
|
Sign up to set email alerts
|

Of texts and practices: Empowerment and organisational cultures in world bank-funded rural development programmes

Abstract: The World Bank's recent concern for 'empowerment' grows out of longer standing discussions of participation, non-governmental organisations (NGOs) and civil society. While commitments to empowerment enter World Bank texts with relative ease, their practice within Bank-funded projects is far more contingent, and the meanings they assume become much more diverse. This paper considers the relationship between such texts and the development practices which emerge, using an analysis of the 'organisational cultures'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 26 publications
0
35
0
1
Order By: Relevance
“…The use of these tools to achieve "self-governance" drew heavily on the discourses on empowerment advocated by the Bank. Central to empowerment is stakeholder control and decision making for ownership and efficiency of the projects, giving voice to the poor and collective action, or "social capital" (Bebbington et al 2007). But this empowerment process also serves neocollectivist redistributive aims.…”
Section: Improving Capacities and Self-governance To Demand State Supmentioning
confidence: 99%
“…The use of these tools to achieve "self-governance" drew heavily on the discourses on empowerment advocated by the Bank. Central to empowerment is stakeholder control and decision making for ownership and efficiency of the projects, giving voice to the poor and collective action, or "social capital" (Bebbington et al 2007). But this empowerment process also serves neocollectivist redistributive aims.…”
Section: Improving Capacities and Self-governance To Demand State Supmentioning
confidence: 99%
“…Instead, a variety of definitions of empowerment have been suggested and utilised, not only amongst development organisations (Bebbington et al, 2007) but also in the academic literature. As an indication of this variety, Ibrahim and Alkire (2007) (Alsop et al, 2006, p. 10).…”
Section: Conceptualising Empowermentmentioning
confidence: 99%
“…In a study of development programme conducted in Bangladesh for instance, the Word Bank reported that empowerment should be seen under the lens of community organization where different stakeholders including international and local institutions and the organisations of the poor interact in order to find ways of translating "textual commitments to empowerment into a range of diverse practices" (Bebbington, Batterbury & Siddiqi, 2007).…”
Section:  Empowermentmentioning
confidence: 99%